Reproductive age modulates the impact of focal ischemia on the forebrain as well as the effects of estrogen treatment in female rats - Selvamani, Amutha (2008)
While human observational studies and animal studies report a neuroprotective role for estrogen therapy in stroke, the multicenter placebo-controlled Women's Health Initiative (WHI) study concluded that hormone therapy increased the risk for stroke in postmenopausal women. The present study therefore tested the hypothesis that estrogen replacement would increase the severity of a stroke-like injury in females when this replacement occurs after a prolonged hypoestrogenic period, such as the menopause or reproductive senescence, but not when given to females that were normally cycling immediately prior to the hormone replacement. Two groups of female rats were used: multiparous females with normal but lengthened estrus cycles (mature adults), and older multiparous females currently in a persistent acyclic state (reproductive senescent). Animals were either used intact, or were bilaterally ovariectomized and immediately replaced with a 17β-estradiol pellet or control pellet. Animals were subject to a forelimb placing test (a test for sensorimotor deficit) and thereafter to middle cerebral artery occlusion (MCAo) by stereotaxic injection of the vasoconstrictive peptide endothelin-1, adjacent to the MCA. One week after stroke, behavioral tests were performed again. Cortical and striatal infarct volume, measured from brain slices, was significantly greater in intact reproductive senescent females as compared to intact mature adults. Furthermore, estrogen treatment to ovariectomized mature adult females significantly reduced the cortical infarct volume. Paradoxically, estrogen treatment to ovariectomized reproductive senescent females significantly increased cortical and striatal infarct volumes as compared to control pellet replaced senescent females. Significant post-stroke behavioral deficit was observed in all groups on the side contralateral to the lesion, while senescent females also exhibited deficits on the ipsilateral side, in the cross-midline forelimb placement test. Using an animal model that approximates the natural ovarian aging process, these findings strongly support the hypothesis that the effectiveness of estrogen therapy in protecting brain health may depend critically on the time of initiation with respect to a female's reproductive status.